Radikalisme, Anti-Amerikanisme, dan Islamofobia - Vicky Izza El Rahma (Jurnal Keislaman, 2020)
Abtrack: Radicalism, anti-Americanism, and Islamophobia are three ‘-ism’s that are being the motive of action for one another. Therefore, the project to tackle all three must be a global agenda that not only involves inter-State governance in the East and West, but also demands the active role of community members, civil society institutions, religious institutions, and media times in each Country. In this paper will be outlined the global paradigm that the world scholars of the world are contemplating in order to overcome all three.